Investigating a student focused e-learning system in higher education: a case study of diploma students / Jamaliah Mohd Taib; Saliza Ramly; Rohana Ramli. - Mohd Taib, Jamaliah; Ramli, Saliza; Ramli, Rohana (UiTM Press, 2016)
Universiti Teknologi MARA (UiTM) has incorporated a Learning Management System (LMS), known as i-Learn, with cloud computing facilities for distribution of course contents, communication, collaboration, content management and assessments. Some studies have found that some learning management systems have followed a static and predefined representation of knowledge with the view to getting the right information to the right person. As a result, these e-learning systems are not beingfully utilized. Many studies have suggested the failure of e-learning can be prevented if an e-learning system can accommodate student expectations of e-learning. In this study, a survey was conducted to investigate diploma level students’ usage of e-learning technologies and also to determine webservices used by the students in their various learning activities. Based on the questionnaires distributed to 112 diploma students at three campuses of a public university, it was found that students did use technologies extensively and they also utilized the i-learn portal and various web services in completing their learning activities. Based on the findings, researcher shave proposed a student focused e-learning system that provides a Personal Learning Environment (PLE) that supports e-learning. It is suggested that a personalized e-learning environment should blend the web services that support e-learning in a hybrid cloud computing environment due to components and resources that can be freely accessed through cloud computing apps with the highest personalization. With the implementation of a hybrid cloud, the administrator would be able to control and maintain the infrastructure of the LMS.